Faktor Risiko Dominan Sarana Sanitasi di Pemukiman Pesisir: Studi Kasus Desa Paku Kecamatan Binuang Kabupaten Polewali Mandar Sulawesi Barat - Rafidah, Rafidah; Hidayat, Hidayat; Azzahra, Khalisa (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Access to good sanitation facilities is a pressing urgency for communities in theregion. One area that has a high level ofdifficulty of sanitation management is quite high is the coastal area. This research aims to analyzethe risk of environmental sanitation facilities, including clean water, latrines, garbage bins and sewerage (SPAL) in theand sewerage (SPAL) in Paku Village, Binuang Sub-district, West Sulawesi.Polewali Mandar Regency, West Sulawesi. This type of research isanalytic observational research with a cross sectional approach and samples were selected using simple random sampling withusing simple random sampling with a sample size of 400 respondents. Based on the results of the study using the bivariate test, it was found that every sanitation facility includingclean water, latrines, trash cans and SPALs have a relationship with the risk of sanitationsanitation facilities where the p value < α 0.05. Based on the Multivariant Testthat has been done, the highest Exp(B) value is obtained, namely garbage (4.499), then latrine (3.819) high risk, then SPAL (3.793) low riskand clean water (3.080) very low risk. Sanitation facilities in coastal areasPaku Village has different levels of risk, but overall, the most risky is trash bins.the most risky is the trash can. The conclusion of this study is that the level ofrisk of sanitation facilities in Paku Village, Binuang Sub-district, Polewali Mandar Regency, West Sulawesi, namely trash cans, which are a very low risk for sanitation facilities.West Sulawesi, namely trash bins which are a very high risk of sanitation facilities, latrines with a very high risk of sanitation facilities.high, latrine risk.